A comparison of responses to raised extracellular potassium and endothelium-derived hyperpolarizing factor (EDHF) in rat pressurised mesenteric arteries - Mathewson, Alastair M.; Dunn, William R. (Public Library of Science, 2014)
The present study examined the hypothesis that potassium ions act as an endothelium-derived hyperpolarizing factor (EDHF) released in response to ACh in small mesenteric arteries displaying myogenic tone. Small mesenteric arteries isolated from rats were set up in a pressure myograph at either 60 or 90 mmHg. After developing myogenic tone, responses to raising extracellular potassium were compared to those obtained with ACh (in the presence of nitric oxide synthase and cyclo- oxygenase inhibitors). The effects of barium and ouabain, or capsaicin, on responses to raised extracellular potassium or ACh were also determined. The effects of raised extracellular potassium levels and ACh on membrane potential, were measured using sharp microelectrodes in pressurised arteries. Rat small mesenteric arteries developed myogenic tone when pressurised. On the background of vascular tone set by a physiological stimulus (i.e pressure), ACh fully dilated the small arteries in a concentration-dependent manner. This response was relatively insensitive to the combination of barium and ouabain, and insensitive to capsaicin. Raising extracellular potassium produced a more inconsistent and modest vasodilator response in pressurised small mesenteric arteries. Responses to raising extracellular potassium were sensitive to capsaicin, and the combination of barium and ouabain. ACh caused a substantial hyperpolarisation in pressurized arteries, while raising extracellular potassium did not. These data indicate that K+ is not the EDHF released in response to ACh in myogenically active rat mesenteric small arteries. Since the hyperpolarization produced by ACh was sensitive to carbenoxolone, gap junctions are the likely mediator of EDH responses under physiological conditions.